Enterobacter cloacae administration induces hepatic damage and subcutaneous fat accumulation in high-fat diet fed mice - Keskitalo, Anniina (PLoS One, 2018)
Accumulating evidence indicates that gut microbiota plays a significant role in obesity, insulin resistance and associated liver disorders. Family Enterobacteriaceae and especially Enterobacter cloacae strain B29 have been previously linked to obesity and hepatic damage. The underlying mechanisms, however, remain unclear. Therefore, we comprehensively examined the effects of E. cloacae subsp. cloacae (ATCC® 13047™) administration on host metabolism of mice fed with high-fat diet (HFD). C57BL/6N mice were randomly divided into HFD control, chow control, and E. cloacae treatment groups. The E. cloacae treatment group received live bacterial cells in PBS intragastrically twice a week, every other week for 13 weeks. Both control groups received PBS intragastrically. After the 13-week treatment period, the mice were sacrificed for gene and protein expression and functional analyses. Our results show that E. cloacae administration increased subcutaneous fat mass and the relative proportion of hypertrophic adipocytes. Both subcutaneous and visceral fat had signs of decreased insulin signaling and elevated lipolysis that was reflected in higher serum glycerol levels. In addition, E. cloacae -treated mice had significantly higher hepatic AST and AST/ALT ratio, and their liver histology indicated fibrosis, demonstrating that E. cloacae subsp. cloacae administration promotes hepatic damage in HFD fed mice.